Neglected paediatric talus neck fracture: a successful clinical outcome without post-traumatic complications - Kusco, Burak; Gurbuz, Kaan; Fatih Dogar (Journal of the Pakistan Medical Association, 2024)
Paediatric talus fracture is an extremely rare type of fracture and occurs due to the structural properties of the elastic cartilage that is resistant to high forces. It has a much lower prevalence than in adults. The axial loading of the talus to the anterior tibia while the ankle is in dorsiflexion is the most common mechanism of talus fractures. Although talus neck fracture is the most common fracture, talus corpus fractures are the second most common. Here we present the case of an adolescent male patient who underwent a successful non-surgical treatment and follow-up of a neglected talus neck fracture. Keywords: Children, Talus, Closed fracture, Avascular necrosis, Outcome.